Diseases having an influence on inhibition of angiogenesis as risk factors of osteonecrosis of the jaw - Paek, Seung Jae; Park, Won-Jong; Shin, Ho-Sung; Choi, Moon-Gi; Kwon, Kyung-Hwan; Choi, Eun Joo (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2016)
The objective of this study was to retrospectively investigate the association of diseases having an influence on inhibition of angiogenesis such as hypertension, diabetes mellitus type II, hypercholesterolemia, and rheumatoid arthritis (RA) with the development of osteonecrosis of the jaws. The 135 patients were allocated into 4 groups of bisphosphonate-related osteonecrosis of the jaw (BRONJ) group (1A); non-BRONJ group (1B); osteonecrosis of the jaw (ONJ) group (2A); and control group (2B), according to histologic results and use of bisphosphonate. This retrospective study was conducted with patients who were treated in one institute from 2012 to 2013. Fisher's exact test and logistic regression analysis were used to analyze the odds ratios of diseases having an influence on inhibition of angiogenesis for development of ONJ. The effects of diabetes and hypertension were not statistically significant on development of ONJ. When not considering bisphosphonate use, RA exhibited a high odds ratio of 3.23 ( =0.094), while hyperlipidemia showed an odds ratio of 2.10 ( =0.144) for development of ONJ. More than one disease that had an influence on inhibition of angiogenesis showed a statistically significant odds ratio of 2.54 ( =0.012) for development of ONJ. Patients without diseases having an influence on inhibition of angiogenesis were at less risk for developing ONJ.